STUDYING OF THE CLIMATIC FACTORS THAT INFLUENCE ON THE GROWTH OF THE SAXAULIN THE SOUTHERN REGION (ҚазҰУ Хабаршысы. География сериясы, 2023)
This article considers the technology of reproduction by monitoring the phytocenotic features, biomorphological and eco-biological conditions of saxaul in the southern region of Kazakhstan. As an environmental issue, the state of saxaul production in the southern regions of Kazakhstan is still not up to date. This is due to the lack of scientifically based agro technology for growing saxaul crops in the wild, the lack of forest seed base and special seeders for sowing saxaul seeds. Therefore, it is necessary to evaluate the existing cultivation technologies and reconsider the idea of ​​saxaul as a plant that can grow in any forest conditions. The research was carried out in the laboratory conditions of the Department of Ecology and Chemistry of the Faculty of Natural Sciences. Geobotanical methods and agrotechnical research methods were used as scientific methods: control of seed planting material of black saxaul.For comparison with wild saxaul species, the expeditionary method, latent, virginal and generative development methods, control methods, and phenological research methods were used. Studies have shown that saxaul seeds can be grown in artificial and field conditions. As a result of the study, it can be predicted that the southern region has the opportunity to increase the number and scale of saxaul species. This fact provides a favorable ecological solution to the environment, that is, the problem of desertification and sand control. The seeds of the black saxaul were planted in laboratory conditions before the seedlings were ready to be transplanted into the natural area.